Bystander Response Following High-Dose X-irradiation; Time-dependent Nature of GammaH2AX Foci and Cell Death Consequences - Fatemeh Pakniyat; Hossein Mozdarani; Hassan Ali Nedaee; Aziz Mahmoudzadeh; Mahdieh Salimi; Somayeh Gholami (Journal of Biomedical Physics and Engineering, 2023)
Background: The paradigm shifts in target theory could be defined as the radiation-triggered bystander response in which the radiation deleterious effects occurred in the adjacent cells. Objective: This study aims to assess bystander response in terms of DNA damage and their possible cell death consequences following high-dose radiotherapy. Temporal characteristics of gH2AX foci as a manifestation of DNA damage were also evaluated.Material and Methods: In this experimental study, bystander response was investigated in human carcinoma cells of HeLa and HN5, neighboring those that received high doses. Medium transfer was performed from 10 Gy-irradiated donors to 1.5 Gy-irradiated recipients. GammaH2AX foci, clonogenic and apoptosis assays were investigated. The gH2AX foci time-point study was implemented 1, 4, and 24 h after the medium exchange. Results: DNA damage was enhanced in HeLa and HN5 bystander cells with the ratio of 1.27 and 1.72, respectively, which terminated in more than two-fold clonogenic survival decrease, along with gradual apoptosis increase. GammH2AX foci temporal characterization revealed maximum foci scoring at the 1 h time-point in HeLa, and also 4 h in HN5, which remained even 24 h after the medium sharing in higher level than the control group.  Conclusion: The time-dependent nature of bystander-induced gH2AX foci as a DNA damage surrogate marker was highlighted with the persistent foci at 24 h. considering an outcome of bystander-induced DNA damage, predominant role of clonogenic cell death was also elicited compared to apoptosis. Moreover, the role of high-dose bystander response observed in the current work clarified bystander potential implications in radiotherapy.